Emerging trends and hotspots in intestinal microbiota research in sepsis: bibliometric analysis - Zhang, Zhengyi; Yang, Meijie; Zhou, Tong; Chen, Yingjie; Zhou, Xiujuan; Long, Kunlan (Frontiers in Medicine, 2024)
Background The association between the gut microbiota and sepsis has garnered attention in the field of intestinal research in sepsis. This study utilizes bibliometric methods to visualize and analyze the literature on gut microbiota research in sepsis from 2011 to 2024, providing a scientific foundation for research directions and key issues in this domain. Methods Original articles and reviews of gut microbiota research in sepsis, which published in English between 2011 and 2024, were obtained from the Web of Science Core Collection on June 21, 2024. Python, VOSviewer, and CiteSpace software were used for the visual analysis of the retrieved data. Results A total of 1,031 articles were analyzed, originating from 72 countries or regions, 1,614 research institutions, and 6,541 authors. The articles were published in 434 different journals, covering 89 different research fields. The number of publications and citations in this research area showed a significant growth trend from 2011 to 2024, with China, the United States, and the United Kingdom being the main research forces. Asada Leelahavanichkul from Thailand was identified as the most prolific author, making him the most authoritative expert in this field. “Nutrients” had the highest number of publications, while “Frontiers in Cellular and Infection Microbiology,” “Frontiers in Immunology” and “the International Journal of Molecular Sciences” have shown increasing attention to this field in the past 2 years. Author keywords appearing more than 100 times included “gut microbiota (GM),” “sepsis” and “microbiota.” Finally, this study identified “lipopolysaccharides (LPS),” “short-chain fatty acids (SCFAs),” “probiotics,” “fecal microbiota transplantation (FMT)” and “gut-liver axis” as the research hotspots and potential frontier directions in this field. Conclusion This bibliometric study summarizes current important perspectives and offers comprehensive guidance between sepsis and intestinal microbiota, which may help researchers choose the most appropriate research directions.